Drivers of Recent North Pacific Decadal Variability: The Role of Aerosol Forcing. Issue 12 (10th December 2021) - Dittus, Andrea J.; Hawkins, Ed; Robson, Jon I.; Smith, Doug M.; Wilcox, Laura J.
Abstract: Climate variability in the Pacific has an important influence on climate around the globe. In the period from 1981 to 2012, there was an observed large‐scale cooling in the Pacific. This cooling projected onto the negative phase of the Pacific Decadal Oscillation (PDO) and contributed to a slowdown in the rate of near‐surface temperature warming. However, this cooling pattern is not simulated well by the majority of coupled climate models and its cause is uncertain. We use large multi‐model ensembles from the sixth Climate Model Intercomparison Project, and an ensemble of simulations with HadGEM3‐GC3.1‐LL that is specifically designed to sample the range of uncertainty in historical anthropogenic aerosol forcing, to revisit the role of external forcings. We show that anthropogenic aerosols can drive an atmospheric circulation response via an increase in North Pacific sea level pressure and contribute to a negative PDO during this period in several global climate models. In HadGEM3, this increase in North Pacific sea‐level pressure is associated with an anomalous Rossby Wave train across the North Pacific, which is also seen in observations. Our results provide further evidence that anthropogenic aerosols may have contributed to observed cooling in the Pacific in this period. However, the simulated cooling in response to aerosol forcing is substantially weaker than the warming induced by greenhouse gases, resulting in simulations that are warming faster than observations, and further highlighting the need to understand whether models correctly simulate atmospheric circulation responses. Plain Language Summary: Climate variability in the Pacific has an important influence on climate around the globe. In the period from 1981 to 2012, there was an observed large‐scale cooling in the Pacific. The causes of this observed cooling are still uncertain. Climate models are able to simulate similar cooling patterns, but these are often weaker than observed. We show that anthropogenic aerosols, tiny particles emitted by human activity, have likely contributed to observed cooling in the Pacific since the 1980s via changes in atmospheric circulation. The simulated response to anthropogenic aerosols is weaker than the warming response to greenhouse gases, resulting in a majority of climate model simulations that are warming faster than observations over this period. We speculate that Pacific cooling induced by atmospheric circulation changes in response to aerosol may be underestimated in current global climate models, but other hypotheses exist, highlighting the need for further research in this area. Key Points: Anthropogenic aerosols can induce an increase in North Pacific sea level pressure in GCMs and promote a negative Pacific Decadal Oscillation over 1981–2012 This circulation‐mediated Pacific cooling in response to anthropogenic aerosol is weaker than GHG‐induced warming GCMs appear unable to capture the strength of the observed cooling in the Pacific during this period and possible causes are discussed